Surgical approach in correction of a crack in the gnathotheca of a black swan (Cygnus atratus, Latham, 1790) - First case report - L. Cazati; M.B. Ferreira; T.B.P. Faiete; G.R.D. Silva; G.S. Xavier; T.D.S. Araujo; G.R. Araujo; C.S. Pizzutto; G.G. Facco (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2023)
ABSTRACT The black swan (Cygnus atratus, LATHAM, 1790) is a bird kept as an ornamental in zoos. Because of their long beaks they tend to have a reserved prognosis in musculoskeletal disorders such as beak trauma, secondary to skull bone fractures, presenting irreversible lesions. The aim of this report is present a clinical surgical innovation in the repair of a black swan’s gnathotheca fissure with the application of non-conventional materials used. It was observed that one of the swans kept in a zoo display area had difficulty feeding, with associated weight loss. It was observed tissue loss and a lacerative lesion in the caudal sublingual region of its beak. The lesion was corrected by a separate simple suture in the cranial region of the beak and with a x-clamping using steel surgical wire and the application of dental resin in the distal region to perform a sustentation bridge in the beak end-gap. After 12 days, the animal was able to feed again and remained perfectly adapted to the restoration, reestablishing the anatomical and physiological function of its beak.